Multiple anthelmintic resistance among dorper sheep detected with phenotypic markers against parasitic gastroenteritis - Noor Al Majidah Abd Majid,; Muhammad Iqbal Ishak,; Jagathis Wee Vanniar Murugapiran,; Nor Azlina Abdul Aziz,; Basripuzi Nurul Hayyan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Parasitic gastroenteritis (PGE) is a significant disease that affects small ruminant production. PGE is controlled exclusively by chemical anthelmintics but restricted by anthelmintic resistance. Hence, dependence on anthelmintics needs to be reduced. This study aimed to investigate the anthelmintic resistance status of a Dorper sheep farm while determining the phenotypic markers of resistance to PGE. Sheep that met the criteria of the Faecal Egg Count Reduction Test (FECRT) were divided into a control and four treatment groups of 11 to 13 animals per group. Faecal and blood samples at pre- and post-treatments were subjected to faecal egg counts (FEC), faecal culture, packed cell volume (PCV) and peripheral eosinophil counts (PEC). The data were analysed by Spearman rank correlation and two-way ANOVA. FECRT showed resistance towards albendazole, levamisole, fenbendazole and ivermectin which was predominated by Haemonchus contortus. Significant negative correlations were observed between FEC and PCV in control (r=-0.88, p<0.01), fenbendazole (r=-0.58, p<0.01) and ivermectin (r=-0.69, p<0.01) groups. Significant positive correlations were detected between FEC and PEC in control (r=0.95, p<0.01) and levamisole (r=0.56, p<0.01) groups. This study shows multiple anthelmintic resistance with promising resistant characteristics against PGE among sheep.